2012
DOI: 10.4236/jwarp.2012.47051
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of SWAT2009 Using Crop Biomass, Evapotranspiration, and Deep Recharge: Calera Watershed in Zacatecas, Mexico Case Study

Abstract: Groundwater is the main source of water in the semi-arid Calera watershed, located in the State of Zacatecas, Mexico. Due to increasing population, rapid industrial growth, and increased irrigation to meet growing food demand, groundwater extraction in the Calera watershed are exceeding recharge rates. Therefore, development and evaluation of alternative water management strategies are needed for sustainable development of the region. The Soil and Water Assessment Tool (SWAT) model was selected for this purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…The values were then manually adjusted until the PB for the crop models reached satisfactory values for cotton (−4.5%), grain sorghum (−27.3%), and winter wheat (−6.0%) from the year 1986 to 2010 ( Figure 4). Manual calibration of the model for yields of cotton, grain sorghum, and winter wheat followed successful hydrologic calibration using percent bias as a measure of performance, which is popularly used in crop-yield modeling studies [41,42]. Yield data were based on the Oklahoma State University experimented variety trials data for the years 2005 to 2010 (http://croptrials.okstate.edu/) and county level crop yield data for the years 1986 to 2005 (Oklahoma Agricultural Statistics database, http://digitalprairie.ok.gov/cdm/ref/collection/stgovpub/id/11177).…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…The values were then manually adjusted until the PB for the crop models reached satisfactory values for cotton (−4.5%), grain sorghum (−27.3%), and winter wheat (−6.0%) from the year 1986 to 2010 ( Figure 4). Manual calibration of the model for yields of cotton, grain sorghum, and winter wheat followed successful hydrologic calibration using percent bias as a measure of performance, which is popularly used in crop-yield modeling studies [41,42]. Yield data were based on the Oklahoma State University experimented variety trials data for the years 2005 to 2010 (http://croptrials.okstate.edu/) and county level crop yield data for the years 1986 to 2005 (Oklahoma Agricultural Statistics database, http://digitalprairie.ok.gov/cdm/ref/collection/stgovpub/id/11177).…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…After achieving a satisfactory streamflow calibration, the model was further calibrated for prediction of cotton lint yield under both irrigated and dryland systems to obtain a good match between the simulated and reported cotton lint yields. Previous SWAT modeling studies that performed crop yield calibration (Hu et al, 2007;Nair et al, 2011;Sarkar et al, 2011;Avila-Carrasco et al, 2012) suggested adjusting the biomass/ energy ratio (BIO_E) and maximum leaf area index (BLAI) to calibrate the SWAT model for crop yield prediction. Among these studies, Sarkar et al Harvest and Kill parameters (Kill on July 1) Default *Auto-irrigation was simulated in appropriate proportion of cotton area based on county cotton irrigation acreage summary reports.…”
Section: Swat Model Calibrationmentioning
confidence: 99%
“…La altitud del acuífero Calera varía entre los 600 y 2000 m, el cual presenta unidades de origen volcánico pertenecientes a la Sierra Madre Occidental, además se forma por materiales aluviales y lacustres de arcilla, limo, arena y grava cementados con arcilla calcárea. La litología corresponde a rocas ígneas, calizas, dolomitas y metamórficas fracturadas por movimientos tectónicos (Ávila et al 2012;Hernández et al 2012;Navarro et al 2005). El tipo de suelo con mayor predominio es el Catañozen lúvico ya que es producto del arrastre del material aluvial que conforma la región (INEGI, 2014).…”
Section: Ubicación Y Caracterización Del áRea De Estudiounclassified